Long-term results of the Latarjet procedure for anterior instability of the shoulder - Mizuno, Naoko; Denard, Patrick J.; Raiss, Patric; Melis, Barbara; Walch, Gilles (Journal of shoulder and elbow surgery, 2014)
BACKGROUND: The Latarjet procedure is effective in managing anterior glenohumeral instability in the short term, but there is concern for postoperative arthritis. The purpose of this study was to evaluate the long-term functional outcome after the Latarjet procedure and to assess the prevalence of and risk factors for glenohumeral arthritis after this procedure. - MATERIALS AND METHODS: A retrospective review was conducted of 68 Latarjet procedures at a mean of 20 years postoperatively. The mean age at surgery was 29.4 years. Functional outcome was determined by the Rowe score, subjective shoulder value, and recurrence of instability. Preoperative arthritis and postoperative radiographs were reviewed to evaluate the development or progression of arthritis. - RESULTS: The mean Rowe score increased from 37.9 preoperatively to 89.6 at final follow-up (P < .001). The mean subjective shoulder value was 90.9% at final follow-up. The postoperative rate of recurrence was 5.9%. Of the 60 shoulders without arthritis preoperatively, 12 (20%) had developed arthritis at final follow-up. Among the 8 shoulders with preoperative arthritis (all stage 1), 4 (50%) demonstrated progression of arthritis at final follow-up. Overall, postoperative arthritis was stage 1 in 14.7%, stage 2 in 5.9%, and stage 3 in 8.8% of cases; no stage 4 arthritis was observed. Risk factors for postoperative arthritis were older age, high-demand sports activity, and lateral overhang of coracoid bone graft. - CONCLUSION: The Latarjet procedure provides excellent long-term outcomes in the treatment of recurrent anterior glenohumeral instability. Twenty years after the Latarjet procedure, arthritis may develop or progress in 23.5% of cases, but the majority of arthritis is mild.